2011
DOI: 10.1111/j.1502-3931.2010.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms and the preservation of the Ediacara biota

Abstract: Laflamme, M., Schiffbauer, J.D., Narbonne, G.M., & Briggs, D.E.G. 2011: Microbial biofilms and the preservation of the Ediacara biota. Lethaia, Vol. 44, pp. 203–213. The terminal Neoproterozoic Ediacaran Period is typified by the Ediacara biota (ca. 579–542 Ma), which includes the first morphologically complex macroscopic organisms. Both the taphonomic setting that promoted the preservation of the soft‐bodied Ediacara biota in coarse‐grained sediments, and the influence of associated microbial coatings on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 46 publications
3
100
0
Order By: Relevance
“…kerogen) and/or soluble carbonaceous materials (Cai et al, 2012;Schiffbauer et al, 2014b;Stankiewicz et al, 2000), as observed in carbonaceous compressions (Xiao et al, 2002), small carbonaceous microfossils (Butterfield and Harvey, 2012), and organically preserved skeletal fossils . Non-biomineralized tissues are also sometimes preserved in siliciclastic rocks as casts, molds, and impressions (Gutiérrez-Marco and García-Bellido, 2015;Muscente and Allmon, 2013), such as Ediacara-type fossils (Laflamme et al, 2011;Narbonne, 2005).…”
Section: Taphonomic Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…kerogen) and/or soluble carbonaceous materials (Cai et al, 2012;Schiffbauer et al, 2014b;Stankiewicz et al, 2000), as observed in carbonaceous compressions (Xiao et al, 2002), small carbonaceous microfossils (Butterfield and Harvey, 2012), and organically preserved skeletal fossils . Non-biomineralized tissues are also sometimes preserved in siliciclastic rocks as casts, molds, and impressions (Gutiérrez-Marco and García-Bellido, 2015;Muscente and Allmon, 2013), such as Ediacara-type fossils (Laflamme et al, 2011;Narbonne, 2005).…”
Section: Taphonomic Processesmentioning
confidence: 99%
“…Overall, the trend broadly follows the prolonged oxygenation of the ocean-atmosphere system (Gill et al, 2011; and the protracted development of the sediment mixed layer (Tarhan et al, 2015), the zone of sediment homogenized and fluidized via bioturbation by burrowing animals, in the early Paleozoic. These changes in marine environments affected exceptional preservation by promoting scavenging of buried carcasses (Allison and Briggs, 1993); enhancing the seawater concentrations of O 2 and SO 4 2 − used in the main microbial metabolisms of decay (Canfield and Farquhar, 2009;Tarhan et al, 2015); deepening the sedimentary aerobic and sulfate reduction zones in which soft tissues are most aggressively degraded Schiffbauer et al, 2014b); and reducing the prevalence of microbial mats, which facilitate authigenic/diagenetic mineralization by sealing fossils off from oxic or suboxic bottom waters (Gehling, 1999;Laflamme et al, 2011) and preventing efflux of precipitating geochemical species (Callow and Brasier, 2009;. Collectively, these changes impacted the likelihood of organic remains surviving long enough to undergo authigenic/diagenetic mineralization prior to their destruction.…”
Section: Exceptional Preservation Through Time In Marine Settingsmentioning
confidence: 99%
“…First, microbial communities can remodel sediments, generating rare but clearly distinguishable features that have been named microbially-induced sedimentary structures (MISS, Gerdes et al, 1993;Hagadorn and Bottjer, 1997;Noffke et al, 2001;Noffke, 2009). MISS have favored preservation of body impressions or the formation of death masks, such as those found in the Ediacaran period (Gehling, 1999;Narbonne, 2005;Laflamme et al, 2011), or footprints of Late Jurassic sauropods (Marty et al, 2010). In addition, the frequent association of bacterial cells with exceptionally preserved fossils supports the link between fossilization and microbial mats.…”
Section: Introductionmentioning
confidence: 99%
“…biogeochemistry | taphonomy | paleontology P ervasive pyritization of soft-bodied organisms is rare but may result in remarkable cellular preservation and provide unique biogeochemical and taphonomic information (1)(2)(3)(4)(5). Pyritic microfossils have been reported from several Precambrian strata (e.g., ref.…”
mentioning
confidence: 99%